Insulin Analogs and Cancer: A Note of Caution - Janssen, Joseph A. M. J. L.; Varewijck, Aimee J. (Frontiers in Endocrinology, 2014)
Abstract In view of the lifelong exposure and large patient populations involved, insulin analogues with an increased mitogenic effect in comparison to human insulin may potentially constitute a major health problem, since these analogues may possibly induce the growth of pre-existing neoplasms. At present, the available data suggest that insulin analogues are safe. In line with these findings, we observed that serum of diabetic patients treated with insulin analogues, compared to that of diabetic patients treated with human insulin, did not induce an increased phosphorylation of tyrosine residues of the insulin-like growth factor-I receptor (IGF-IR). However, the classical model of the IGF-IR signaling may be insufficient to explain (all) mitogenic effects of insulin analogues since also non-canonical signaling pathways of the IGF-IR may play a major role in this respect. Although phosphorylation of tyrosine residues of the IGF-IR is generally considered to be the initial activation step within the intracellular IGF-IR signaling pathway, it has been found that cells undergo a signaling switch under hyperglycemic conditions. After this switch, a completely different mechanism is utilized to activate the mitogenic (mitogen-activated protein kinase (MAPK) pathways of the IGF-IR that is independent from tyrosine phosphorylation of the IGF-IR. At present it is unknown whether activation of this alternative intracellular pathway of the IGF-IR occurs during hyperglycemia in vivo and whether it is stronger in patients treated with (some) insulin analogues than in patients treated with human insulin. In addition, it is unknown whether the insulin receptors (IRs) also undergo a signaling switch during hyperglycemia. This should be investigated in future studies. Finally, relative overexpression of IR isoform A (IR-A) in (pre) cancer tissues may play a key role in the development and progression of human cancers during treatment with insulin (analogues). Further studies ar